The "castle" sememe in Slavic fairy tales - Danišová, Nikola (Slavia Centralis, 2022)
The present paper focuses on the material identification and basic typological classification of the "castle" as a sememe in the Slavic fairy tales. Through intertextual and intercultural confrontation, we will try to reveal the constitutive principles of depicting the castle, i.e. to find out what narrative situations and subject-motivic constellations this sememe is iconised in, and clarify its function and archetypal meaning in the metaphoric code of the Slavic fairy tales. We assume that the “castle” in the world of fairy tales and magic stories represents a distinctive and distinguished topos, which is an integral part of the "hero´s journey" (Campbell), and/or his initiation (Propp, Hodrová), or the process of individualisation (Jung, Bettelheim, Hollis). The present paper is the primary probe into the chosen topic.
Keywords: architextual themathology; interpretation; slavic fairy tale; castle